Breast cancer related lymphedema in patients with different loco-regional treatments - GÜLLÜOĞLU, MAHMUT BAHADIR (CHURCHILL LIVINGSTONE, 2012)
Introduction: Lymphedema, a sequela of breast cancer and breast cancer therapy, changes functional abilities and may affect a patient's psychosocial adjustment and overall quality of life. Aim of this prospective observational study was to determine the rate of mid-term and late time period lymphedema in breast cancer patients with different loco-regional treatments, and factors associated with lymphedema. Materials and methods: Patients surgically treated for early-stage breast cancer were prospectively enrolled in the study. Demographic, clinical, pathological, and loco-regional treatments data of patients and lymphedema rates were recorded. Patients were divided into six groups regarding different loco-regional treatments. Pre- and postoperative (12 months, and median 64 months after surgery) circumferences of arms were recorded. Results: 218 patients, all female with a median age of 48 (19-82) years, were included in the study. The numbers of patients in breast conservation surgery group (BCS) (N = 104), mastectomy group (N 114), sentinel lymph node biopsy group (SLNB) (N = 80), axillary lymph node dissection group (ALND) (N = 138), group with radiotherapy (RT) (N = 88) and group without radiotherapy (N = 130). Incidence of lymphedema after surgery in mid-term period was 24.8%. The rate of lymphedema at 64 months median follow-up time was 7.3%. (BCS: 11.1%, 4.2% and 0.5%; Mastectomy: 15.0%, 3.2% and 1.4%; SLNB: 8.0%, 1.9% and 0.5%; ALND: 18.0%, 5.3% and 1.4%; RT: 14.7%, 6.3% and 1.4%; without RT: 11.4%, 2.1% and 0.5%). When we excluded patients with both mid-term and late term lymphedema, only four patients developed lymphedema at late time, then re-calculated late term lypmhedema rate was 1.8%. The factors affecting the lymphedema was ALND and radiotherapy (RT) and no lymphedema was detected in patients underwent breast conserving surgery and SLNB. Age and body mass index were not related to lymphedema at any time. Conclusion: The incidence of lymphedema gradually increased in time and a quarter of patients experienced the complication at the end of year. The rate of lymphedema in patients with ALND was significantly higher than patients with SLNB alone. If RT added to SLNB the lymphedema rate was getting higher than SLNB alone. In all patients lymphedema rate was decreased one year after the surgery and further decreased at median 64 months follow-up time period. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Breast cancer; Lymphedema; Axillary dissection; Sentinel lymph node biopsy; Radiotherapy; SENTINEL-NODE BIOPSY; EDEMA FOLLOWING TREATMENT; AXILLARY DISSECTION; ARM EDEMA; RISK-FACTORS; FOLLOW-UP; MORBIDITY; WOMEN; PREVALENCE; CARCINOMA